Dreamfever : a novel - Moning, Karen Marie (Moning, Karen Marie. Fever series, 2009)
Atlanta suburb resident MacKayla Lane discovers her ability to see into the realm of the Fae after the devastating murder of her sister and attracts the unwanted attention of Seelie, vampire, and human assassins.